Evaluasi dan Optimalisasi Aspek Teknik Operasional Sistem Pengelolaan Sampah di Kecamatan Kapuas Kabupaten Sanggau - Ayuni, Nurul; Jati, Dian Rahayu; Winardi, Winardi (Universitas Tanjungpura, 2025)
The waste management system in Kapuas Sub-district still uses the old paradigm without prior processing. As the waste generation increases, the landfill capacity will decrease faster, so an alternative solution is needed to reduce the landfill load through a waste management mechanism. The method of measuring waste generation and composition refers to SNI 19-3964-1994. Evaluation of operational technical aspects is carried out through observation and interviews with related parties then comparing the data obtained with the comparison indicators of Permen PU No. 03/PRT/M/2013 then from the evaluation results, recommendations for waste management systems can be given. The results of the research obtained, namely the amount of waste generated in Kapuas District is 2.17 l / person / day and the most dominant waste composition is organic waste 45.22% and inorganic waste in the form of plastic 36.83% and paper 10.84%. The existing condition of the waste management system in Kapuas Sub-district shows that the aspects of containerization, collection, transfer and transportation mostly meet the criteria of Permen PU No. 03/PRT/M/2013, while the aspects of processing and final processing do not meet the criteria of Permen PU No. 03/PRT/M/2013 so that the recommendations given by building waste processing facilities and changing the method in the landfill to controlled landfill and the need to provide socialization and education to the community regarding the waste management system. Through evaluation of the technical aspects of operation.